(untitled) (Bangladesh Journal of Medicine, 2015)
Background: Rheumatoid arthritis is a chronic, autoimmune, inflammatory disorder of unknown aetiology that is characterized by symmetric synovitis and the propensity to cause joint destruction, disability and premature death. Disease-modifying anti-rheumatic drugs (DMARDs) slow the natural course of the disease, reduce joint damage and pain, and retard loss of function and disability. Disease modifying agents should be started as early as possible. A number of studies demonstrating the effectiveness of combinations of DMARDs in early RA. Methods: This is a comparative descriptive type of study was conducted in the Department of Medicine, Rangpur Medical College and Hospital, Rangpur & Medicine Specialists Chambers, Rangpur, over a period of 2 (two) years from July 2010 to June 2012 on newly diagnosed RA patients on the basis of ACR criteria. The 30 patients were divided into 3 groups. Group I got MTX, Group II got SSZ and Group III got MTX & SSZ. Purposive consecutive sampling method was employed. The objective of the study was to evaluate the outcome of patients of rheumatoid arthritis treated with MTX or SSZ alone versus MTX and SSZ in combination. The primary outcome measure was change in DAS28. Results: The mean DAS 28 score baseline was found 7.23±0.44 in group I, 7.29±0.39 in group II and 7.86±0.41 in group III. The mean DAS 28 score end of the study was 4.24±0.39 in group I, 4.85±0.54 in group II and 3.08±0.36 in group III. The difference was statistically significant (P<0.001) among the three groups. There is no toxicity found in any group. Regarding side effects, the difference was not statistically significant (P>0.05) among the three groups. Conclusion : This study suggests that the mean changes in the DAS28 score significantly lower in those who received combination therapy compared with those who received either MTX or SSZ alone during one year follow up. Bangladesh J Medicine Jul 2015; 26 (2) : 67-75